1998
DOI: 10.1021/jm9707131
|View full text |Cite
|
Sign up to set email alerts
|

Selective Endothelin A Receptor Antagonists. 3. Discovery and Structure−Activity Relationships of a Series of 4-Phenoxybutanoic Acid Derivatives

Abstract: The third in this series of papers describes our further progress into the discovery of a potent and selective endothelin A (ETA) receptor antagonist for the potential treatment of diseases in which a pathophysiological role for endothelin has been implicated. These include hypertension, ischemic diseases, and atherosclerosis. In earlier publications we have outlined the discovery and structure-activity relations of two moderately potent series of nonpeptide ETA receptor antagonists. In this paper, we describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…An illustrative example of such an optimization strategy has been described for the endothelin A receptor (Scheme ). Astles and co‐workers had developed two compound series which were originally derived from the same 3D database query 72. Thus, it was conceived that these series might share a common binding mode, but no molecular alignment could be found that matched all relevant pharmacophores of the corresponding compounds.…”
Section: Ligand‐based Drug Designmentioning
confidence: 99%
See 1 more Smart Citation
“…An illustrative example of such an optimization strategy has been described for the endothelin A receptor (Scheme ). Astles and co‐workers had developed two compound series which were originally derived from the same 3D database query 72. Thus, it was conceived that these series might share a common binding mode, but no molecular alignment could be found that matched all relevant pharmacophores of the corresponding compounds.…”
Section: Ligand‐based Drug Designmentioning
confidence: 99%
“…The hydrophobic groups are shown by the green circles, while the acid functions are shown by the red circles. 72 B) The two compounds could not be aligned in a way that all important pharmacophoric groups were matched. The hypothesis of a cationic interaction center on the receptor (blue circle) allowed the two series to be merged by assuming that the acidic groups interact with this center from different directions.…”
Section: Ligand‐based Drug Designmentioning
confidence: 99%
“…The generation of a pharmacophore hypothesis can be ligand based or may be derived from the protein 3D structure (if available) by a hot spot analysis (programs GRID [11,156], LUDI [35], DrugScore [49,157,158]). For 3D searches the programs Catalyst [e.g., 78,81,82,88,91,104,115,138,153,155] and Unity [e.g., 78,122,139,140,145,146,150,154,167] are most often used. LigandScout is a new program for the automated generation of pharmacophore hypotheses from 3D structures of proteinligand complexes [164].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacophore-based database searching is a proven method for lead identification [7,8,9] and continues to provide an alternative or a complement to high-throughput screening for this purpose. 4.11 [116]. Endothelin antagonists have provided an important target for drug-discovery efforts.…”
Section: Lead Generationmentioning
confidence: 99%